Răspuns :
Răspuns:
Explicație pas cu pas:
6x²=(radical din 30-3radical din6)² si extragi radicalul de ordinul 2:
xrad6 = +- (radical din 30-3radical din6)
x = +-(rad5 x rad6 / rad6 - 3rad6 / rad6) =
+-(rad5 - 3)
x1 = 3 - rad5
x2 = rad5 - 3.
[tex]\displaystyle\bf\\6x^2=\Big(\sqrt{30}-3\sqrt{6}\Big)^2\\\\6x^2=\Big(\sqrt{6\cdot5}-3\sqrt{6}\Big)^2\\\\6x^2=\Bigg(\sqrt{6}\Big(\sqrt{5}-3\Big)\Bigg)^2\\\\6x^2=\Big(\sqrt{6}\Big)^2\cdot\Big(\sqrt{5}-3\Big)^2\\\\6x^2=6\Big(\sqrt{5}-3\Big)^2~~~\Big|~:6\\\\x^2=\Big(\sqrt{5}-3\Big)^2~~~\Big|~\sqrt{~~}\\\\x=\pm\Big(\sqrt{5}-3\Big)\\\\\boxed{\bf x_1=\sqrt{5}-3}\\\\\boxed{\bf x_2=3-\sqrt{5}}[/tex]